Sapindaceae endémicas del Perú - León, Blanca (2006)
The Sapindaceae are represented in Peru by 22 genera and around 190 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly lianas, trees and vines. Here we recognize 16 species and one variety as endemics in seven genera. Paullinia is the genus with more endemic species. Endemic taxa are found in Humid Lowland Amazonian Forests, Very Humid Montane Forests and Very Humid Premontane Forests regions, between 100 and 2900 m elevation. Four endemic Sapindanceae species have been recorded within Peru’s protected areas system.